2020
DOI: 10.1016/j.ekir.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Medication Discrepancies and Hospitalization Risk Among Patients With Advanced CKD

Abstract: This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). M edication discrepancies are common in medicine, posing an ongoing threat to safe patient care. Discrepancies can be defined as any difference between the physician's records and the medications that the patient actually takes, including related dose and frequency. In clinical practice, medication discrepancies are common, occurring in 34% to 95% of patients newly admitted to hospitals. 1,2 The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although this study was not adequately powered to evaluate whether eKidneyCare can avert serious ADRs, we did observe a 60% rate reduction in discrepancies that could seriously harm patients and result in emergency room visits and hospitalization. The possibility of increased health care utilization is supported by recent evidence demonstrating an association between medication discrepancies and hospitalization in patients with CKD (28). Finally, eKidneyCare breaks down medication data silos, which studies have shown magnify medication errors (29,30), by allowing all users access to a common clinic pharmacy database and through secure communication channels, seamlessly connecting all stakeholders so that issues surrounding medication safety can be addressed quickly and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was not adequately powered to evaluate whether eKidneyCare can avert serious ADRs, we did observe a 60% rate reduction in discrepancies that could seriously harm patients and result in emergency room visits and hospitalization. The possibility of increased health care utilization is supported by recent evidence demonstrating an association between medication discrepancies and hospitalization in patients with CKD (28). Finally, eKidneyCare breaks down medication data silos, which studies have shown magnify medication errors (29,30), by allowing all users access to a common clinic pharmacy database and through secure communication channels, seamlessly connecting all stakeholders so that issues surrounding medication safety can be addressed quickly and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Considering these factors, the risk for adverse drug events is high. [7][8][9][10][11][12][13][14] Improperly prescribed medications in CKD have led to adverse outcomes. 15,16 A recent Canadian primary care resource outlined key CKD medications to be dose adjusted or avoided.…”
Section: Introductionmentioning
confidence: 99%